Sociology of Dakwah: Scientific Alternative Social Conflict Resolution Religious - Nurkhalis Nurkhalis (Jurnal Community, 2015)
History records since 1789 which lasted throughout the 19th century - were confronted by an important event full of chaos, the French Revolution - became the forerunner of human social distortions in dunua at that time. One side of the revolution demonstrate positive change and social order on the other side is going through a critical phase to be part concerns some scientists. However, who would have thought excessive attention and seriousness of the leading scientists cultivated by August Comte and Emile Durkheim. Ultimately leading trigger of Sociology and the validity of the methodology laid Sociology as a science. Who would have thought from then until now, to contribute to the presence of study Sociology 'partnership' as; Political Sociology, Economic Sociology, Sociology of Law, Sociology of Religion, Sociology of Communication and so on. Not without reason that 'partnership' Sociology is a solution of the situation and condition of polemics, discrimination, marginalized, alienation had stripped many aspects of life. Even for a man as the main mission of peace and compassion presenters also increasingly disoriented. It would need to design an alternative social science that is Sociology Propagation, scientific consists of scientific foundation; Sociology itself, the science of Communications and Propagation Studies.